2003
DOI: 10.1038/sj.bjp.0705050
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of β2‐adrenoceptor‐mediated responses by short‐acting β2‐adrenoceptor agonists in human lung mast cells

Abstract: 1 The principal aim of the present study was to determine whether long-term treatment of human lung mast cells (HLMC) with the clinically-relevant b 2 -adrenoceptor agonists, salbutamol and terbutaline, leads to desensitization of b 2 -adrenoceptor-mediated responses in these cells. 2 The non-selective b-adrenoceptor agonist, isoprenaline, and the selective b 2 -adrenoceptor agonists, salbutamol and terbutaline, inhibited the IgE-mediated release of histamine from HLMC. Salbutamol (pD 2 ; 7.7+0.3) and terbutal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
(38 reference statements)
4
34
0
2
Order By: Relevance
“…[17][18][19] In the present study, we found that IgE-dependent histamine release from cultured human mast cells was inhibited significantly by isoproterenol, salbutamol, fenoterol, and clenbuterol and that the inhibition was apparently attenuated by prolonged treatment with the agonists. On the other hand, although forskolin, an activator of adenylate cyclase, 28,29) apparently inhibited histamine release from cultured mast cells, it did not cause an attenuation of the inhibition even after prolonged treatment for up to 240 min.…”
Section: Effects Of Pretreatment For 3 Dsupporting
confidence: 54%
See 1 more Smart Citation
“…[17][18][19] In the present study, we found that IgE-dependent histamine release from cultured human mast cells was inhibited significantly by isoproterenol, salbutamol, fenoterol, and clenbuterol and that the inhibition was apparently attenuated by prolonged treatment with the agonists. On the other hand, although forskolin, an activator of adenylate cyclase, 28,29) apparently inhibited histamine release from cultured mast cells, it did not cause an attenuation of the inhibition even after prolonged treatment for up to 240 min.…”
Section: Effects Of Pretreatment For 3 Dsupporting
confidence: 54%
“…11,13,14) On the other hand, desensitization has also been observed in the inhibition of human mast cell histamine release by b 2 -adrenoceptor agonists. [17][18][19] Chong and Peachell 18) reported that isoproterenol inhibition of histamine release from human lung mast cells is considerably more susceptible to desensitizing treatments than the isoproterenol relaxation of bronchial smooth muscle. In contrast to histamine release, however, desensitization of PGD 2 and LT release inhibition by b 2 -adrenoceptor agonists has rarely been investigated.…”
mentioning
confidence: 99%
“…Previous studies have shown that b-adrenergic agonists can also increase cAMP in mast cells, and can inhibit mast cell activation as a result (Church and Hiroi, 1987;Weston and Peachell, 1998). However, because b-adrenergic receptors on mast cells tend to internalize and desensitize once bound by agonists, the capacity of b-adrenergic receptor agonists to maintain high cAMP levels in mast cells is limited (Church and Hiroi, 1987;Chong et al, 2003;Scola et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term exposure (few seconds) to b 2 -adrenoceptor agonists results in receptor phosphorylation by both cAMP-dependent protein kinase A (PKA) and G-protein receptor kinase (GRK), whereas long-term exposure to b 2 -adrenoceptor agonists includes downregulation of surface receptor numbers (which involves internalization and degradation of the receptors; Carter & Hill, 2005) and results in changes in the transcription of b-adrenoceptors or mRNA stability (Yanagawa et al 2016). A reduction in b 2 -adrenoceptor mRNA after incubation with b 2 -adrenoreceptor agonists are consistent with decreased synthesis of b 2 -adrenoceptors after prolonged agonist contact; this amount is independent of continued occupation of b 2 -adrenoceptors on the cell surface (Chong et al 2003). Studies indicated that GRK-catalyzed phosphorylation of G-protein-coupled receptors (GPCR) followed by b-arrestin binding are key steps in the internalization of receptors or in receptor desensitization.…”
Section: Introductionmentioning
confidence: 94%
“…Previous work from our laboratory has shown that long-term exposure of HLMC to b-agonists attenuated the subsequent ability of the agonists to inhibit histamine release (Chong et al 2003;Bastan et al 2014). As phosphorylation of b 2 -adrenoceptors is perhaps essential in inducing desensitization in many cells, including mast cells, this study sought to investigate the importance of phosphorylation events in mast cells by targeting some of their protein phosphatases.…”
Section: Introductionmentioning
confidence: 99%